Analyse des terres cuites architecturales de l’aqueduc de Nyon/Colonia Iulia Equestris (Suisse) - Benjamin Clément; Christophe Henny; Anne Schmitt (Gallia)
During the excavations carried out since 2013 by Archeodunum on the Swiss section of the “Divonne-les-Bains – Nyon” aqueduct, a programme to analyse the structure and its surroundings was initiated by the Vaud Canton Archaeology department. Add to this end, all the terracotta bricks making up the bottom of the canal (specus) were sampled for the purpose of exhaustive study, entailing both a metrological and typological investigation and physico-chemical analyses of the clay of which they are composed.Probably built during the 1st century AD, the Colonia Iulia Equestris aqueduct would have supported the development of the Roman city founded in the middle of the previous century on the shores of Lake Geneva. In the absence of dating evidence for the construction itself, the establishment of public baths near the colony’s forum at the beginning of the 1st century AD provides us with a chronological clue to its construction. The analytical aspect of the architectural terracotta used for this aqueduct comprises 52 elements taken from nine different sections, spread over the downstream two-thirds of its route. Two types of materials were used for paving the bottom of the specus: Lydian module bricks (1.5 ft × 1 ft square), on the one hand, and bipedal bricks (2 ft square) on the other.Through the physico-chemical analyses conducted on the clays of these architectural terracottas, we were better able to determine the origin of the materials. In the central part of the structure, the four sections excavated on the territory of the Swiss municipalities of Crassier and Borex were built with Lydian bricks produced in a single workshop, called “Gp4”. In the sections uncovered at the entrance to the settlement, less than a kilometre from the urban centre, there is a diversification of supply sources, with materials mainly from the “Gp4” workshop supplemented by bricks produced in three other workshops: “Gp1” and “Gp5” –also found in the settlement– and the “Iso 2” workshop, which matches a single production. For the bipedal bricks, it can also be seen that the materials used come from two different workshops: one part comes from workshop “Gp4”, while one brick was produced in a second isolated workshop, “Iso 1”.The twofold approach to the terracotta construction materials of the aqueduct shows the use of bricks with a homogeneous module that perfectly matches the dimensions used for the laying of the specus. From Divonne to the entrance to the settlement, the bricks seem to have been supplied by a single workshop “Gp4”. Although its exact location is still unknown, it is to be found near the route of the aqueduct, probably upstream rather than downstream. However, this assumption needs to be qualified for the immediate vicinity of the settlement. Indeed, a diversification in the sources of architectural terracotta can be observed, while the same modules are retained. This scenario allows us to propose two hypotheses: the construction of the aqueduct by one team working in successive sections and obtaining supplies close to each section; or the construction of this work by several teams working at the same time on successive sections with their own supplies.